The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00420-007-0199-7
|View full text |Cite
|
Sign up to set email alerts
|

Particulate air pollution and vascular reactivity: the bus stop study

Abstract: PM(2.5) may reduce the capacity to vasodilate, a potential explanation for the documented association with cardiovascular morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…Assessed as an overall effect, this change in brachial artery caliber is similar to that observed in a previous study by our group (7), which found an average 0.11-mm decrease in BAd 30 minutes after exposure to DE at 200 mg/m 3 . This finding adds to the growing body of literature confirming that acute exposure to traffic-related air pollutants has a consistent and measurable effect on vasocontractility (7,(14)(15)(16)(17)(18) associated with a simultaneous rise in systemic blood pressure (9,19). Interestingly, in this study, we found evidence that both genetic variations and AO supplementation may alter individual susceptibility to the DE exposure.…”
Section: Discussionsupporting
confidence: 75%
“…Assessed as an overall effect, this change in brachial artery caliber is similar to that observed in a previous study by our group (7), which found an average 0.11-mm decrease in BAd 30 minutes after exposure to DE at 200 mg/m 3 . This finding adds to the growing body of literature confirming that acute exposure to traffic-related air pollutants has a consistent and measurable effect on vasocontractility (7,(14)(15)(16)(17)(18) associated with a simultaneous rise in systemic blood pressure (9,19). Interestingly, in this study, we found evidence that both genetic variations and AO supplementation may alter individual susceptibility to the DE exposure.…”
Section: Discussionsupporting
confidence: 75%
“…In healthy adults, very short-term exposure to elevated levels of ambient PM from traffic sources while exercising for 30 minutes near roadways 195 and when resting by bus stops for 2 hours 196 has been related to impaired endothelium-dependent vasodilation. Daily changes in ambient gaseous pollutants (SO 2 and NO x ) in Paris, France, have also been associated with impaired endothelium-dependent vasodilation among nonsmoking men.…”
Section: Vascular Functionmentioning
confidence: 99%
“…Epidemiological studies demonstrate that present -day levels of PM are capable of elevating arterial blood pressure (BP) within a period of a few days (Linn et al, 1999 ;Brauer et al, 2001 ;Ibald -Mulli et al, 2001, 2004Zanobetti et al, 2004 ;Chuang et al, 2005 ;Santos et al, 2005 ;Harrabi et al, 2006 ;Madsen and Nafstad, 2006 ;Choi et al, 2007 ;Liu et al, 2007 ;McCracken et al, 2007 ;Auchincloss et al, 2008 ;Dvonch et al, 2009 ;Brook et al, 2010 ). Controlled human and animal experiments have corroborated the veracity of this relationship under certain scenarios whereby BP can increase within only hours of exposure (Gong et al, 2003 ;Mills et al, 2005Mills et al, , 2007Mills et al, , 2008Urch et al, 2005 ;Dales et al, 2007 ;Br ä uner et al, 2008 ;Fang et al, 2008 ;Shah et al, 2008 ;Brook et al, 2009 ).…”
Section: Introductionmentioning
confidence: 90%
“…There have been fi ve positive and negative studies each (Table 18.2 ) (Gong et al, 2003 ;Mills et al, 2005Mills et al, , 2007Mills et al, , 2008Urch et al, 2005 ;Dales et al, 2007 ;Br ä uner et al, 2008 ;Fang et al, 2008 ;Shah et al, 2008 ;Brook et al, 2009 ). As with the epidemiology, most of these protocols were not designed with the explicit intent to focus on BP changes as the primary outcome.…”
Section: Controlled Exposure Studiesmentioning
confidence: 99%